2021
DOI: 10.1002/pd.6071
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal phenotype of 47, XXY (Klinefelter syndrome)

Abstract: Objective: There is a paucity of knowledge regarding the prenatal presentation of Klinefelter syndrome, or 47, XXY. Accurate prenatal counseling is critical and in utero diagnosis is currently limited by a poor understanding of the prenatal phenotype of this condition.Methods: This is a case series of fetuses with cytogenetically confirmed 47, XXY in the prenatal period or up to age 5 years, with prenatal records available for review from four academic institutions between 2006 and 2019. Ultrasound reports wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…A multicentre cohort study analysed the frequency of abnormal pregnancy ultrasound ndings in children diagnosed with Klinefelter syndrome pre-or postnatally and found that nearly one third of the cases had structural abnormalities, most commonly intracranial and skeletal abnormalities (29). The inclusion criteria for the children with Klinefelter syndrome were similar to our study.…”
Section: Discussionsupporting
confidence: 75%
“…A multicentre cohort study analysed the frequency of abnormal pregnancy ultrasound ndings in children diagnosed with Klinefelter syndrome pre-or postnatally and found that nearly one third of the cases had structural abnormalities, most commonly intracranial and skeletal abnormalities (29). The inclusion criteria for the children with Klinefelter syndrome were similar to our study.…”
Section: Discussionsupporting
confidence: 75%
“…52 While 45,X may present with a prenatal phenotype such as cystic hygroma or bicuspid aortic valve, the prenatal phenotypes for 47,XXY, 47,XYY or 47,XXX are more likely to be normal. 53 Prenatal detection of SCAs is important, as it allows for genetic counseling and preparation for an infant that may have physical differences and unique health needs. For patients with 47,XXX, this may include assessment for hypotonia, monitoring of developmental milestones or evaluation for seizure activity.…”
Section: Bias Assessmentmentioning
confidence: 99%
“…13 For 47,XXY, a fetal phenotype is also emerging, which includes increased firsttrimester nuchal translucency ( >3.0 mm) noted in 6/26 (23.1%) and second-trimester anomalies (CNS, cardiac, echogenic bowel, and limb abnormalities) in 7/24 (29.2%). 16 Of note, the degree of maldevelopment of the systems is variable with CNS findings ranging from mild ventriculomegaly to holoprosencephaly and the skeletal findings including a unilateral clubfoot to shortened long bones. 16 Further work is needed to develop the 47, XXY fetal phenotype as these observations are from a cohort of 41 fetuses.…”
Section: Definition Of Sex Chromosome Aneuploidymentioning
confidence: 99%
“…16 Of note, the degree of maldevelopment of the systems is variable with CNS findings ranging from mild ventriculomegaly to holoprosencephaly and the skeletal findings including a unilateral clubfoot to shortened long bones. 16 Further work is needed to develop the 47, XXY fetal phenotype as these observations are from a cohort of 41 fetuses. Although children with 47,XXY have higher incidences of developmental delay, learning disability, and behavioral issues, and in the adult, the effects of gonadal dysgenesis include infertility and osteoporosis, structural anomalies have not been associated with the overall phenotype.…”
Section: Definition Of Sex Chromosome Aneuploidymentioning
confidence: 99%